Foreign Currency Denominated Assets and International Shock Absorption in Switzerland and Japan - Gunther Schnabl (Center for Economic Studies and ifo Institute (CESifo), 2015)
Currencies of countries with persistent current account surpluses and high foreign currency denominated assets such as the Swiss franc and Japanese yen are under a persistent appreciation pressure, what restricts the degree of freedom in the choice of exchange rate regime. Official announcements (implicit communication) of appreciations can trigger runs into the domestic currency, which make appreciation expectations self-fulfilling. The resulting negative growth effect is likely to trigger interest rate cuts, which can add to unsustainable financial exuberance. It is argued that horizontal exchange rate pegs are the most effective tool to stabilize economies with large net foreign asset positions.
Keywords: F15; F31; F33; 330; international investment position; appreciation-induced risk; exchange rate risk; foreign exchange intervention; monetary policy independence; Switzerland; Japan